The development of initial material of spring common wheat for breeding for resistance to stem rust (Puccinia graminis Pers. f. sp. tritici), uncluding race Ug99, in Russia - I. F. Lapochkina; O. A. Baranova; V. P. Shamanin; G. V. Volkova; N. R. Gainullin; A. V. Anisimova; D. N. Galinger; E. N. Lazareva; E. V. Gladkova; O. F. Vaganova (Вавиловский журнал генетики и селекции)
Donors of resistance of common wheat to stem rust race Ug99 (breeding lines GT 96/90, 113/00i-4 and 119/4-06rw) are involved in cross breeding with the use of the step crossing and backcrossing method. While developing hybrids with the spring mode of life, donor of resistance 113/00i-4 (Sr2, Sr36, Sr39, Sr40, Sr44, Sr47) and accession 145/05i, which is resistant to leaf rust under the conditions of the RF Central Region but susceptible to Ug99, were used for backcrossing, 137 individual plants with the homozygotic state of alleles of 2–5 genes of resistance to stem rust were selected from the obtained hybrid families F4–F5 and backcross progeny BC1F3-BC2F2-BC3F2 by means of molecular markers. The progeny of these individual plants was tested in the North Caucasian and West Siberian regions of the RF for natural populations of stem and leaf rust and for powder mildew in the Central Region. The lines resistant to these diseases were estimated as to the other economically valuable features: plant height, number of days before heading, ear productivity, weight of 1,000 grains, protein and gluten content in grain, 71 spring wheat line with multiple resistance to two or three diseases and the development of best agronomic characters were selected for the Central region and 20 lines were selected for West Siberia for further testing of their competitiveness with the best varieties and lines in the breeding nurseries. As a result of the work, original source material was developed with several spring wheat resistance genes to Ug99.